A benchmark case for aeroacoustic simulations involving fluid-structure-acoustic interaction transferred from the process of human phonation - Schoder, Stefan; Falk, Sebastian; Wurzinger, Andreas; Lodermeyer, Alexander; Becker, Stefan; Kniesburges, Stefan (Acta Acustica, 2024)
Modeling fluid-structure-acoustic interaction is a highly challenging task and currently there is a lack of available benchmark datasets. For instance, to understand the processes of human phonation, it is essential to fully understand the fluid-structure-acoustic interaction process. In this article, a synthetic human phonation model is presented for benchmarking numerical methods in the field of aerodynamics, aeroacoustics and the highly-complex fluid-structure-acoustic interaction process of the voice production. The objective is to present the wide range of experimental data available, including the model geometry, the material characteristics, quantitiesreferred to the vocal fold dynamics, fluid mechanical quantities and the acoustic field. Firstly, the experimental setup is specified. Secondly, the experimental data is described in detail, accompanied by illustrations. Having the dataset in hand, finally, it is shown how to use this data to validate a computational phonation model called simVoice successfully. In conclusion, this benchmarking dataset offers the opportunity to validate structural dynamics, aerodynamics and aeroacoustics of a highly-complex fluid-structure-acoustic interaction simulation, obtained from different mathematical formulations and numerical procedures.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Benchmark dataset; Fluid-structure-acoustics interaction; Human voice production; SimVoice; SynthVoice

Acoustic and Aerodynamic Coupling during Phonation in MRI-Based Vocal Tract Replicas - Probst, Judith; Lodermeyer, Alexander; Fattoum, Sahar; Becker, Stefan; Echternach, Matthias; Richter, Bernhard; Döllinger, Michael; Kniesburges, Stefan (Applied Sciences, 2019)

Acoustic characterization of an averaged vocal tract model based on the MRI data of professional tenors - Probst, Judith; Lodermeyer, Alexander; Fattoum, Sahar; Echternach, Matthias; Becker, Stefan; Kniesburges, Stefan (Proceedings of the International Congress on Acoustics, 2019)
Human speech is created in the larynx and the vocal tract. For vowels, the basic sound is generated by the oscillating vocal folds and filtered by the vocal tract to produce the typical formants. In the present study, we investigate the influence of the vocal tract on phonation. Based on Magnet Resonance Imaging (MRI) data, the acoustic behavior of the vocal tract can be characterized using numerical and experimental models. However, previous studies only analyzed single vocal tracts that were directly obtained from individuals. To investigate the basic influence of the vocal tract on phonation, a vocal tract model is necessary that shows preferably little individual but the typical acoustic characteristics of the specific vowel. Hence, we computed an average vocal tract geometry based on six simplified individual vocal tracts that were extracted from MRI images of professional tenors. The resulting vocal tract model was evaluated in an experimental setup including artificial vocal folds. The comparison with the tenors' vocal recordings shows that the model reproduces the acoustic properties well. Hence, the average vocal tract model presented here is suitable for future investigations of the influence of the vocal tract on phonation.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Artificial vocal fold models; Vocal tract acoustics; Voice production modeling

Aeroacoustic analysis of the human phonation process based on a hybrid acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Becker, Stefan; Döllinger, Michael; Birk, Veronika; Kniesburges, Stefan (Experiments in Fluids, 2018)
The detailed analysis of sound generation in human phonation is severely limited as the accessibility to the laryngeal flow region is highly restricted. Consequently, the physical basis of the underlying fluid–structure–acoustic interaction that describes the primary mechanism of sound production is not yet fully understood. Therefore, we propose the implementation of a hybrid acoustic PIV procedure to evaluate aeroacoustic sound generation during voice production within a synthetic larynx model. Focusing on the flow field downstream of synthetic, aerodynamically driven vocal folds, we calculated acoustic source terms based on the velocity fields obtained by time-resolved high-speed PIV applied to the mid-coronal plane. The radiation of these sources into the acoustic far field was numerically simulated and the resulting acoustic pressure was finally compared with experimental microphone measurements. We identified the tonal sound to be generated downstream in a small region close to the vocal folds. The simulation of the sound propagation underestimated the tonal components, whereas the broadband sound was well reproduced. Our results demonstrate the feasibility to locate aeroacoustic sound sources inside a synthetic larynx using a hybrid acoustic PIV approach. Although the technique employs a 2D-limited flow field, it accurately reproduces the basic characteristics of the aeroacoustic field in our larynx model. In future studies, not only the aeroacoustic mechanisms of normal phonation will be assessable, but also the sound generation of voice disorders can be investigated more profoundly.

Aeroacoustic and vibroacoustic mechanisms during phonation - Lodermeyer, Alexander; Mohamadi Bagheri, Eman; Näger, Christoph; Nusser, Katrin; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (13th International Conference on Advances in Quantitative Laryngology, Voice and Speech Research, 2019)

Aeroacoustic sound generation during phonation - analysis of acoustic analogies for a hybrid acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (11th International Conference on Voice Physiology and Biomechanics, 2018)

Aeroacoustic sound generation during phonation - analysis of acoustic analogies for a Hybrid Acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (11th Internation conference on voice physiology and biomechanics, 2018)

Aeroacoustic sound generation during phonation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Tautz, Matthias; Becker, Stefan; Döllinger, Michael (Journal of the Acoustical Society of America, 2016)

Aeroacoustic sound generation during phonation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Tautz, Matthias; Döllinger, Michael; Becker, Stefan (Fortschritte der Akustik – DAGA 2017, 2017)

A hybrid acoustic PIV approach to characterize sound generation in a human larynx model - Lodermeyer, Alexander; Becker, Stefan; Mohamadi Bagheri, Eman; Tautz, Matthias; Döllinger, Michael; Kniesburges, Stefan (19th International Symposium on the Application of Laser and Imaging Techniques to Fluid Mechanics, 2018)

A laser-based technique to evaluate sound generation during phonation - Lodermeyer, Alexander (FAU University Press, 2020)
Investigating aeroacoustic sound generation in a measurement is challenging since the flow field needs to be highly resolved in the temporal and spatial domain. Thus, complex aeroacoustic phenomena like the mechanisms of the human voice are still not fully captured scientifically. Recent advances in optical technologies have pushed the limits of measurement resolution and accuracy, making aeroacoustic investigations potentially accessible. Therefore, as a first part of this thesis, a measurement technique is implemented that applies a hybrid acoustic PIV (HAcouPIV) approach. State-of-the-art measurement technology is combined with most recent numerical strategies in the field of acoustics. High-speed PIV is applied to determine the flow velocity, and a numerical approach computes the pressure field based on the measurement data. Then, a perturbation approach is applied to separate the sound pressure from the fluid-mechanical pressure fluctuations. In the second part of the thesis, the HAcouPIV technique is employed to investigate the sound-generating mechanisms and its radiation during human phonation. Thereby, for the first time, the acoustic source field is extracted based on a combination of experimental measurements and numerical simulations. A highly modulated source field that reaches into the supraglottal region was found as the most significant sound-generating mechanism of the phonatory process. This was shown for both broadband and harmonic content. The analysis of the vibroacoustic behavior of the vocal fold oscillation based on laser-vibrometry data revealed strong harmonic content in the glottal region of the superior vocal fold surface. Hence, it potentially contributes to a strong fluid-structure-acoustic interaction especially for the harmonic content. In conclusion, the hybrid approach of laser-based measurement techniques and numerical evaluation procedures was successfully applied. It substantiates the fundamental mechanisms that form the basis of sound generation during phonation. These results suggest to focus on the modulation of the glottal jet and its entire spatial expansion as the main component for sound generation during voiced speec
Keywords: Fluid-Struktur-Akustik Interaktion; Messtechnik; Particle Image Velocimetry; Phonation; Schallentstehung; Stimmhaftes Sprechen; menschliche Stimme Vibrometrie; acoustics; fluid mechanics; fluid-structure-acoustic interaction; human voice; laser; measurement technology; particle image velocimetry; phonation; sound generation; structural mechanics; vibrometry; voiced speech; Akustik; Strömungsmechanik; Strukturmechanik; Fluid-Struktur-Wechselwirkung; Schallerzeugung; Stimmgebung; Stimme; Laser; Strömungsmesstechnik; Akustische Messtechnik; Particle-Image-Velocimetry; Vibrometer

Analysis of improved pulsating heat pipe designs for hot spot applications - Schwarz, Florian; Messmer, Pascal; Lodermeyer, Alexander; Danov, Vladimir; Fleßner, Christian; Becker, Stefan; Hellinger, Rolf (International Journal of Heat and Mass Transfer, 2022)
Pulsating heat pipes (PHPs) are increasingly used for the thermal management of hot spots. A major goal in the design process of PHPs is the handling of high heat fluxes and, thus, improved thermal resistance. The thermal resistance can be reduced by increasing the latent or convective heat transfer. Two design approaches with that goal are presented in this study: a flower-shaped PHP design to increase the latent heat transfer and a star-shaped PHP design to increase the convective heat transfer. We compare the proposed designs to a state-of-the-art, meander-shaped PHP design. Thereby, we quantify the thermal performance and the flow pattern of the different PHP designs. The copper PHPs were filled with acetone and tested horizontally and vertically. The filling ratios varied from 0 % to 90 % and the heat inputs increased from 50 W to 200 W. Our results illustrate that the flower-shaped PHP design reduces the thermal resistance by 7 % in horizontal and 12 % in vertical position. We found a strong interrelation between flow pattern and heat transfer in PHPs. Our study shows that phase change plays a key role for the thermal resistance. Based on that, we provide design criteria to optimize the thermal capabilities of PHPs with a special focus on hot spots.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 0000; 1111; Flower-shaped PHP; Hot spots; Oscillating heat pipe (OHP); Power electronics; Pulsating heat pipe (PHP); Radial PHP; Star-shaped PHP; Thermal management

Analysis of the tonal sound generation during phonation with and without glottis closure - Kniesburges, Stefan; Lodermeyer, Alexander; Semmler, Marion; Schulz, Yvonne; Schützenberger, Anne; Becker, Stefan (Journal of the Acoustical Society of America, 2020)

A time-resolved PIV-based methodology to analyse the acoustics of human phonation - Lodermeyer, Alexander; Mohamadi Bagheri, Eman; Näger, Christoph; Nusser, Katrin; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (13th International Symposium on Particle Image Velocimetry – ISPIV 2019, 2019)

Effect of the ventricular folds in a synthetic larynx model - Kniesburges, Stefan; Birk, Veronika; Lodermeyer, Alexander; Schützenberger, Anne; Bohr, Christopher; Becker, Stefan (Journal of Biomechanics, 2017)
EVALuna2:33181

Effects of the vocal tract on phonation threshold pressure - Fulcher, Lewis; Becker, Stefan; Kniesburges, Stefan; Lodermeyer, Alexander; Kähler, George; Döllinger, Michael (11th Internation conference on voice physiology and biomechanics, 2018)

Einfluss der Stimmlippenoberfläche und asymmetrischer Elastizitätsmodule auf die Phonation - Peters, Gregor; Lodermeyer, Alexander; Kutz, Anne; Gröhn, Franziska; Becker, Stefan (Fortschritte der Akustik – DAGA 2017 (Kiel, 03/06/17 - 03/09/17), 2017)

Geometry of the Vocal Tract and Properties of Phonation near Threshold: Calculations and Measurements - Fulcher, Lewis; Lodermeyer, Alexander; Kähler, George; Becker, Stefan; Kniesburges, Stefan (Applied Sciences, 2019)

High-speed and Phase-averaged PIV in a synthetic human larynx model - a comparative analysis - Lodermeyer, Alexander; Kniesburges, Stefan; Tautz, Matthias; Döllinger, Michael; Birk, Veronika; Becker, Stefan (18th International symposium on applications of laser techniques to fluid mechanics, 2016)

Interaction of flow pattern and heat transfer in oscillating heat pipes for hot spot applications - Schwarz, Florian; Uddehal, Shabhrish Reddy; Lodermeyer, Alexander; Mohamadi Bagheri, Eman; Forster-Heinlein, Brigitte; Becker, Stefan (Applied Thermal Engineering, 2021)
Oscillating heat pipes (OHP) are increasingly used for the thermal management of hot spots. Thereby, a local evaporation zone occurs that is still not fully understood due to complex interactions of flow patterns and heat transfer. This study quantifies the thermal performance and the flow behavior of oscillating heat pipes with a centrally located hot spot heater. The copper OHPs were filled with acetone and tested with different orientations. The filling ratios varied from 0% to 90%, the heat inputs increased from 25 W to 200 W. Our results illustrate that the flow velocity values and the resulting thermal resistance are highly interrelated. Within one channel, there is a wide range of velocity values from 30 mm/s to 1200 mm/s; the thermal resistance decreases with higher average flow velocity. By characterizing the flow regime, we show that a reliable start-up depends on the initial vapor liquid pattern. Depending on the initial pattern, an individual temperature difference is required for the start-up, even for similar operating conditions. The analysis of the stopping behavior shows that a uniform temperature difference of 14 K is required for a stable fluid oscillation. Our study substantiates a strong interrelation between flow pattern and heat transfer in OHPs, which also shows a strong potential for future optimizations of OHP applications.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Electronics Cooling; Oscillating Heat Pipe (OHP); Power Electronics; Pulsating Heat Pipe (PHP); Thermal Management

Lokalisierung und Charakterisierung aeroakustischer Quellen mittels laserbasierter Strömungsmessungen - Lodermeyer, Alexander; Becker, Stefan; Mohamadi Bagheri, Eman; Tautz, Matthias; Kniesburges, Stefan ('Fortschritte der Akustik - DAGA 2018, 2018)

Phase-locked flow field analysis in a synthetic human larynx model - Lodermeyer, Alexander; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (Experiments in Fluids, 2015)

Phase-locked flow field analysis in a synthetic human larynx model - Lodermeyer, Alexander; Becker, Stefan; Kniesburges, Stefan; Döllinger, Michael (17th International symposium on applications of laser techniques to fluid mechanics, 2014)

Phonation threshold pressure and the properties of the vocal tract - Fulcher, Lewis; Lodermeyer, Alexander; Kniesburges, Stefan; Kähler, George; Döllinger, Michael; Becker, Stefan (Journal of the Acoustical Society of America, 2017)

Simulating Wind Noise with Airflow Speed-Dependent Characteristics - Mirabilii, Daniele; Lodermeyer, Alexander; Czwielong, Felix; Becker, Stefan; Habets, Emanuël (International Workshop on Acoustic Signal Enhancement, IWAENC 2022 - Proceedings, 2022)
Generating noise samples is crucial in developing and testing noise reduction algorithms or training deep learning models. This work proposes a wind noise generation model with airflow speed-dependent features. A linear predictive analysis of wind noise measured in a wind tunnel at different flow velocities was carried out. This analysis showed that temporal and spectral features depend on the flow speed. The prediction residual's statistics and the filter coefficients are first extracted and then modeled based on the flow speed. The obtained models are then combined to synthetically generate wind noise given a time-varying flow speed profile as input, in contrast to an existing framework where temporal and spectral features were assumed speed-invariant. A subjective evaluation is carried out to assess the perceptual authenticity of the generated noise compared to the existing method.
CRIS-Team Scopus Importer:2022-11-25
Keywords: analysis; synthesis; Wind noise

Simulation of Sound Radiation based on PIV Measurements - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Kaltenbacher, Manfred; Döllinger, Michael; Kniesburges, Stefan; Becker, Stefan (ICTCA 2017 - Book of Abstracts, 2017)

The mechanisms of harmonic sound generation during phonation: A multi-modal measurement-based approach - Lodermeyer, Alexander; Mohamadi Bagheri, Eman; Kniesburges, Stefan; Näger, Christoph; Probst, Judith; Döllinger, Michael; Becker, Stefan (Journal of the Acoustical Society of America, 2021)
Sound generation during voiced speech remains an open research topic because the underlying process within the human larynx is hardly accessible for direct measurements. In the present study, harmonic sound generation during phonation was investigated with a model that replicates the fully coupled fluid-structure-acoustic interaction (FSAI). The FSAI was captured using a multi-modal approach by measuring the flow and acoustic source fields based on particle image velocimetry, as well as the surface velocity of the vocal folds based on laser vibrometry and high-speed imaging. Strong harmonic sources were localized near the glottis, as well as further downstream, during the presence of the supraglottal jet. The strongest harmonic content of the vocal fold surface motion was verified for the area near the glottis, which directly interacts with the glottal jet flow. Also, the acoustic back-coupling of the formant frequencies onto the harmonic oscillation of the vocal folds was verified. These findings verify that harmonic sound generation is the result of a strong interrelation between the vocal fold motion, modulated flow field, and vocal tract geometry.
CRIS-Team Scopus Importer:2021-11-26

The mechanisms of subharmonic tone generation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Becker, Stefan; Traxdorf, Maximilian; Döllinger, Michael (Journal of the Acoustical Society of America, 2016)
EVALuna2:33182

Thermodynamic Analysis of the Dryout Limit of Oscillating Heat Pipes - Schwarz, Florian; Danov, Vladimir; Lodermeyer, Alexander; Hensler, Alexander; Becker, Stefan (Energies, 2020)

Vibrations as a cause of texture defects during the acid-induced coagulation of milk – Fluid dynamic effects and their impact on physical properties of stirred yogurt - Körzendörfer, Adrian; Temme, Philipp; Lodermeyer, Alexander; Schlücker, Eberhard; Hinrichs, Jörg (Journal of Food Engineering, 2021)